Infrared study of trifluoroacetic acid unpurified synthetic peptides in aqueous solution: Trifluoroacetic acid removal and band assignment - Valenti, Laura Elisa (2011)
Synthetic peptide or protein samples are mostly unpurified with trifluoroacetic acid (TFA) used during the synthesis procedure, which strongly interferes with structure determination by infrared (IR) spectroscopy. The aim of this work was to propose a simple strategy to remove TFA contribution from attenuated total reflection (ATR)-IR spectra of the hexahistidine peptide (His6) in aqueous solution to study the conformation of this synthetic peptide without previous purification. Such a strategy is based on the subtraction mode widely employed to remove water contribution, and it is tested with TFA unpurified histidine as a model system. The subtraction is based on eliminating the strong TFA bands at 1147 and 1200 cm-1 by applying a scaling factor (as in buffer correction). The proposed modes represent excellent strategies that do not modify spectral features, and they provide reliable routines to obtain the synthetic peptide spectrum without TFA contribution. The conformational information from the corrected spectra at different pH values is deduced from semiempirical calculated IR spectra of different His6 conformers. The spectral features and the band positions of the corrected spectrum suggest that the peptide molecules mainly adopt an intermolecular β-sheet structure.